Influence of Children's Characteristics and Volunteer Learning Communication Style on Children's Cultural Literacy in Busa Pustaka - Putri Sugiati; Budhi Waskito; Noning Verawati (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of children's characteristics and volunteers’ learning communication styles on children's cultural literacy in Busa Pustaka. Using a quantitative approach and survey method, the study involved 50 child respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that both children's characteristics and the volunteers' communication style significantly influence children's cultural literacy. Volunteers’ communication style was found to have a more dominant effect. These findings emphasize the need for culturally responsive teaching strategies that align with children's developmental characteristics to foster cultural understanding and appreciation.